Agents of institutional change in EU policy: the social investment moment. Issue 6 (3rd June 2018) - de la Porte, Caroline; Natali, David
ABSTRACT: The contribution addresses – through actor-centred historical institutionalism – why and how social investment (SI) emerged at the European Union (EU) level. SI policies built on the institutional basis of the policy co-ordination processes in employment and social inclusion, which originated in the late 1990s and early 2000s. The pre-existent processes represented the necessary but not sufficient condition for the EU SIP to materialise. The decisive factor was the activity of three types of entrepreneurs – intellectual, bureaucratic and political – that enabled the crystallization of the EU Social Investment package (SIP) through issue-framing, institutional alignment and consensus-building. Despite this, the SIP of 2013 ended as a 'social investment moment' that rapidly lost momentum because no additional measures such as indicators or funds were integrated with SIP. Furthermore, the Commission's political priorities changed and the key entrepreneurs that had been active for the materialisation of the SIP were no longer centre stage. The continued presence of former influential entrepreneurs in the EU policy arena, although in different roles, may enable integration of EU SI into new EU social policy initiatives.